PENGARUH PARTISIPASI ANGGARAN TERHADAP KINERJA MANAJERIAL DENGAN PERSEPSI KEADILAN ANGGARAN DAN KOMITMEN TUJUAN ANGGARAN SEBAGAI VARIABEL INTERVENING (Studi Kasus pada Universitas Diponegoro) - Zahro, Hanifatuz; Januarti, Indira (Department of Accounting, Faculty of Economics & Business,Diponegoro University, Indonesia, 2016)
This study aims to examine the influence of budget participation to managerial performance. It also to examine whether perception of distribution budgetary fairness, perception of procedural budgetary fairness and goal commitment mediate the relationship of budget participation and managerial performance.This study used questionnaires and interview to collecting data. From 189 questionnaires were given to managers in Diponegoro University. The questionnaires that complete the answers were 72 questionnaires. Path analysis was utilized to examine the direct and indirect effects of budget participatio to managerial performance. The results of this study showed that budget participation has a direct effect to managerial performance. Budget participation also has a positive effect to perception of distribution budgetary fairness, perception of procedural budgetary fairness and goal commitment. But budget participation didn’t has indirect effect to managerial performance with perception of distribution budgetary fairness, perception of procedural budgetary fairness and goal commitment as intervening variables